Circular polarized microstrip radiant system for 2.4 GHZ RFID aplications. - García Quintana, Raunel; Marante Rizo, Francisco (Telemática, 2022)
The present research work proposes the design and simulation of a pentagonal patch antenna with circular polarization for the 2.4 GHz band by means of electromagnetic coupling in a single layer. The proposed configuration aims to be used in RFID (Radio Frequency Identification) systems to achieve good radiation characteristics when sending or receiving data from the RFID tags implanted in the objects to be identified, keeping the design as simple as possible. Circular polarization is obtained through the electromagnetic coupling technique by modifying the dimensions of the antenna feed line and is optimized by introducing disturbances in the geometry of the patch. The proposed antenna has small and acceptable dimensions for possible use in portable RFID readers, a gain of approximately 1.642 dB at 2.44 GHz, impedance matching and circular polarization bandwidths of 111.6 MHz and 138 MHz, which represents a 4.75% and 5.65% respectively of the center frequency of the working band.